2016
DOI: 10.1038/onc.2015.478
|View full text |Cite
|
Sign up to set email alerts
|

MUC5AC interactions with integrin β4 enhances the migration of lung cancer cells through FAK signaling

Abstract: MUC5AC is a secretory mucin aberrantly expressed in various cancers. In lung cancer, MUC5AC is overexpressed in both primary and metastatic lesions; however, its functional role is not well understood. The present study was aimed at evaluating mechanistic role of MUC5AC on metastasis of lung cancer cells. Clinically, the overexpression of MUC5AC was observed in lung cancer patient tissues and was associated with poor survival. In addition, the overexpression of Muc5ac was also observed in genetically engineere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 57 publications
5
75
2
Order By: Relevance
“…24 Besides, silencing of MUC5AC participated in decreased proliferation and metastatic properties of lung cancer cells through the regulation of FAK signaling. 16 Our results indicated that, in colon cancer, the inhibition of MUC5AC could significantly induce the apoptosis and cell cycle arrest and also repress the metastatic properties of the colon cancer cell line SW620.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…24 Besides, silencing of MUC5AC participated in decreased proliferation and metastatic properties of lung cancer cells through the regulation of FAK signaling. 16 Our results indicated that, in colon cancer, the inhibition of MUC5AC could significantly induce the apoptosis and cell cycle arrest and also repress the metastatic properties of the colon cancer cell line SW620.…”
Section: Discussionmentioning
confidence: 89%
“…15 MUC5AC knockdown resulted in significantly decreased expression of integrins (a5, b1, b3-b5) and the phosphorylation of FAK, leading to the impaired ability of migration in the lung cancer cell line. 16 Of note, the mechanisms of oncoprotein MUC5AC in colon cancer need to be further identified.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were incubated in a humidified atmosphere at 37°C with 5% CO 2 . Human specific MUC16-shRNA (pSUPER-Retro-shMUC16 seq1 and pSUPER-Retro-shMUC16 seq2) and mouse specific pSUPER-Retro-shmuc16 constructs were used for stable transfection of MUC16 in H292, H1975 and K1418 with respective control shRNA (4,22). …”
Section: Methodsmentioning
confidence: 99%
“…Animals that were positive for Kras G12D were infected with AdCre-Luciferase retroviral vector intra-nasally (University of Iowa, Gene and vector core, Iowa, USA). Eight weeks post-infection, the animals were injected with luciferin intra-peritoneally to monitor the tumor growth (22). Mice were fed with food and water ad libitum and subjected to 12 hrs light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation